Letter to Assembly Candidates from J.K. (Ken) MacDonald - J.K. (Ken) MacDonald:::::: (1976)
This letter from Assemblyman J. K. (Ken) Macdonald of California's Thirty-Sixth District to several Assembly candidates, including Jane Tolmach. Macdonald expresses respect for the candidates' willingness to address important state issues and emphasizes the importance of conducting campaigns with integrity, candor, and ethical standards. He notes that while only one candidate will win the office, all can contribute positively to public understanding and respect for government through honorable conduct. Macdonald offers the assistance of his district and Capitol staff in providing information about state operations and legislative activities. He also invites the candidates to meet with him personally to discuss complex issues, with arrangements to be made through his administrative secretary.